A selective approach towards synthesis of poly (3‑bromo thiophene)/graphene quantum dot composites via in-situ and ex-situ routes: Application in light emission and photocurrent generation. (1st January 2021) - Sardar, Soumen; Roy, Indranil; Chakraborty, Subhadeep; Ghosh, Abhisek Brata; Bandyopadhyay, Abhijit
Highlights: Smart conducting polymer-GQD composites synthesised through ex-situ and in-situ routes. Polymer-filler interface quality found dependant on fabrication route. The in-situ composite showed superior photophysical and photo-electrochemical properties while ex-situ composite displayed acceptable photo-electrochemical property only. Abstract: This article elucidates fabrication of a smart composite from poly (3-bromothiophene) (PTBr) and graphene quantum dot (GQD) through facile in-situ and ex-situ routes and demonstrates their photo-physical and photo-electrochemical behaviors. 3-bromothiophene was first polymerized to poly (3-bromothiophene) (PTBr) in presence of graphene oxide (GO) and then converted into PTBr/GQD composite through solvo-thermal route in the in-situ process while in the ex-situ process, both graphene oxide (GO) and poly (3-bromothiophene) (PTBr) were first combined ex-situ and then solvo-thermally treated to fabricate the PTBr/GQD composite. Spectroscopic findings indicate safe formation of the composites however, alteration in both precursor and fabrication route had simultaneously created a demonstrable difference in interfacial interaction between poly (3-bromothiophene) (PTBr) and graphene quantum dot (GQD) which eventually impacted their application behavior. Microscopy, Energy dispersive X-Ray (EDX) mapping and X-ray diffraction study mutually elucidated the formation of uniformly thin, fibrillar (8 nm) over-growth of amorphous poly (3-bromothiophene) (PTBr) over graphene quantum dot (GQD) in the ex-situ composite while in the in-situ composite a comparatively non-uniform and thicker over-growth (12 nm) of poly (3-bromothiophene) (PTBr) over graphene quantum dot (GQD) was noticed. Both the composites had shown quenched photoemission but exhibited a much improved photocurrent generation than the pristine components. However, relatively high concentration of poly (3-bromothiophene) (PTBr) coupled with its stronger interaction with graphene quantum dot (GQD) in the in-situ composite had produced a stronger red shift and much higher photocurrent efficiency than that in the ex-situ sample. Graphical abstract: Image, graphical abstract